Enhancing Collaborative Ideation in Organizations - Paulus, Paul B.; Baruah, Jonali; Kenworthy, Jared B. (Frontiers in Psychology, 2018)
Extensive research and theory has focused on organizational innovation and the organizational factors that influence that innovation. Research on teams has highlighted a similar set of factors as important for team innovation. However, these literatures have not provided a clear picture of the key factors that influence the creative processes in group interactions that occur in teams and organizations. The group creativity literature has provided a strong theoretical and empirical basis for understanding these processes and the conditions required for optimizing creativity in group interactions. We provide the theoretical and empirical basis for a pragmatic approach to enhancing group creativity in various organizational settings.